2018
DOI: 10.1093/pubmed/fdx175
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Health Handbook use for maternal and child care: a cluster randomized controlled study in rural Java, Indonesia

Abstract: MCHHB use promoted continuous care acquisition and care at home from pregnancy to early child-rearing stages in rural Java.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(113 citation statements)
references
References 23 publications
4
99
0
10
Order By: Relevance
“…This is a study protocol for a cRCT aimed at estimating the impact of an intervention package-including the distribution of MCH handbook and its supplementary interventions to pregnant women, compared with the traditional use of two stand-alone HBRs on the utilisation of services provided at healthcare facilities from pregnancy through the postnatal and early childhood period. Few studies have shown that proper utilisation of HBRs could promote continuity of maternal and child health care [14,16,35], and WHO recommends that each pregnant woman carries her own HBRs during pregnancy to improve continuity and quality of care [36]. Notwithstanding, the superiority of the integrated MCH handbook over other alternatives is an area of research in which there is a dearth of gold standard trials [15,37].…”
Section: Discussionmentioning
confidence: 99%
“…This is a study protocol for a cRCT aimed at estimating the impact of an intervention package-including the distribution of MCH handbook and its supplementary interventions to pregnant women, compared with the traditional use of two stand-alone HBRs on the utilisation of services provided at healthcare facilities from pregnancy through the postnatal and early childhood period. Few studies have shown that proper utilisation of HBRs could promote continuity of maternal and child health care [14,16,35], and WHO recommends that each pregnant woman carries her own HBRs during pregnancy to improve continuity and quality of care [36]. Notwithstanding, the superiority of the integrated MCH handbook over other alternatives is an area of research in which there is a dearth of gold standard trials [15,37].…”
Section: Discussionmentioning
confidence: 99%
“…Stunted growth in children who are less than 2 years old is still responsive, meaning it is preventable through intervention (Prendergast & Humphrey, 2014). The MCH handbook contains comprehensive information that can be used to promote better health care and improve the health status of mothers during pregnancy as well as providing guidelines for raising their children (Bhuiyan et al, 2018;Osaki et al, 2019) in a continuous manner (Osaki et al, 2015). The benefit increases for the parents of LBWB or prematurely born babies who are in need of a higher standard of care (Mousavi et al, 2016); therefore, it is crucial that the health care team provide psycho-social support and appropriate health counseling that matches the parents' needs (Kuo et al 2012;Mousavi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the benefits of owning and using the MCH handbook have been done many times, some of which are the studies on the users of services for infants and children, which lead to changes in the level of knowledge and self-confidence and ultimately improve the mothers' capacity to provide care at home. A study on the use of the MCH handbook for neonatal care users covers topics, such as early breastfeeding initiation, immediate breastfeeding, exclusive breastfeeding, and introduction to complementary food from breast milk, vitamin A intake, and the rate of morbidity and mortality among neonatal infants (Yanagisawa et al, 2015;Mori et al, 2015;Osaki et al, 2015;Osaki et al, 2019). Meanwhile, the studies on children focus on immunization visits, visits by health care providers in the event of specific conditions (Upper Respiratory Tract Infection (URTI), fever, and diarrhea), providing proper nourishment, consuming a variety of food, training children to eat on their own, monitoring the occurrence of underweight children and stunted growth, and delays in the child's cognitive growth (Usman, Akhtar, Habib, & Jehan, 2009;Usman et al, 2011;Dagvadorj, et al, 2017;Osaki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Despite less quantitative data on MNCH outcomes, there were significant data from the qualitative and quantitative studies, as well as from the respondents in this study, that emphasized that women, caregivers, and health care workers value HBRs. 3,6,7 There is evidence that they can improve patient-provider communication, continuity of care, 7,9 and increase women's feelings of control and empowerment. 7,10 Including and empowering women and children by encouraging them and their caregivers to be health literate and actively participate in their own care is a key step toward achieving universal health coverage.…”
Section: Introductionmentioning
confidence: 99%